2004
DOI: 10.1111/j.1432-1033.2004.04354.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the substrate specificity of a β‐glycosidase from Spodoptera frugiperda using site‐directed mutagenesis and bioenergetics analysis

Abstract: The specificity of the Spodoptera frugiperda digestive b-glycosidase (Sfbgly50) for fucosides, glucosides and galactosides is determined by noncovalent interactions of glycone 6-OH and glycone 4-OH with the active-site residues Q39 and E451. Site-directed mutagenesis and enzyme steadystate kinetics were described, showing that replacement of E451 with glutamine increased the preference of Sfbgly50 for glucosides in comparison to galactosides, whereas replacing E451 with serine had the opposite effect. In contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 23 publications
1
12
0
1
Order By: Relevance
“…The double mutations modify k cat 10 2 -to 10 3 -fold, whereas K m presents smaller changes. This pattern was also observed for the single mutations of residues Q39 and E451 (12,13). Thermal inactivation experiments showed that the structures of the A451E39 and S451E39 double mutants are similar to the wild-type Sfβgly (t ½ ~1.2 min at 50°C), suggesting that the mutational effects on k cat did not result from large structural modifications of the protein.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…The double mutations modify k cat 10 2 -to 10 3 -fold, whereas K m presents smaller changes. This pattern was also observed for the single mutations of residues Q39 and E451 (12,13). Thermal inactivation experiments showed that the structures of the A451E39 and S451E39 double mutants are similar to the wild-type Sfβgly (t ½ ~1.2 min at 50°C), suggesting that the mutational effects on k cat did not result from large structural modifications of the protein.…”
Section: Resultssupporting
confidence: 56%
“…These single mutations caused a large reduction in the k cat /K m ratio for the hydrolysis of NPβglycosides due to a reduction of about 70% in the energy of the interactions formed by Q39 and E451 with the substrate in the ES ‡ complex (13). Double mutants of Sfβgly (A451E39, S451E39 and S451N39) were prepared by site-directed mutagenesis, expressed in BL21 DE3 cells in order to determine interactions between sites of mutation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kinetics from mutations D84A, R97A, S247A, N249A, F251A, F334A, L350A, K366A and Y420A are new data presented here. Remaining kinetic data collected from 1: Mendonça and Marana, 2011 [9]; 2: Marana et al ., 2002 [7]; 3: Marana et al ., 2004 [8]; 4: Tamaki et al ., 2014 [14]; 5: Mendonça and Marana, 2008 [11]; 6: Marana et al ., 2003 [6]. For calculation of Relative k cat / K m , each k cat / K m mut was compared to the k cat / K mWT data presented on the same manuscript in which the mutant enzyme was firstly described: 1: Mendonça and Marana, 2011 [9]; 2: Marana et al ., 2002 [7]; 3: Marana et al ., 2004 [8]; 4: Tamaki et al ., 2014 [14]; 5: Mendonça and Marana, 2008 [11]; 6: Marana et al ., 2003 [6] (*: This mutant was studied using MUβglc as substrate).…”
Section: Resultsmentioning
confidence: 99%
“…Methods based on HPLC or thin layer chromatography separations to estimate produced sugars have also been described (Adams & Drew, 1965; Berlin et al , 2006; Chundawat et al , 2008). To further characterize the activity of specific cellulolytic enzymes, activity is measured by spectrophotometry using substrates containing p ‐nitrophenol (Terra et al , 1979; Chipoulet & Chararas, 1985a; Cazemier et al , 1997; Marana et al , 2000; Ferreira et al , 2001; Marana et al , 2004; Yapi et al , 2009) or methyl‐umbelliferyl (MU) groups (Jacobson & Schlein, 1997; Marana et al , 2001).…”
Section: Quantitative and Qualitative Detection Of Cellulolytic Activmentioning
confidence: 99%